PENINGKATAN JIWA FOODPRENEUR REMAJA MELALUI PELATIHAN OLAHAN IKAN BANDENG BERBASIS VIDEO EDUKASI MUARA GEMBONG - Artanti, Guspri Devi; Yulianti, Yeni; Maulida, Alvina Fadila; Putri, Dyah Ayu Kensasmi; Ghaisani, Nailah (LPPM Universitas Nusa Mandiri, 2026)
The problems faced by teenagers in the coastal area of Muara Gembong are the limited knowledge and interest in entrepreneurship based on local food potential, especially fishery products, and the lack of contextual learning media that encourages economic independence from school age. This community service activity aims to foster a spirit of food entrepreneurship among teenagers through training in milkfish processing based on educational videos at SMAN 1 Muara Gembong. The approach used is participatory training, which is carried out through lectures, the use of educational videos, food processing practices, and simple business simulations including packaging, labelling, and product marketing. Data collection instruments included knowledge tests, video assessment questionnaires, and participant satisfaction surveys, with data analysis using descriptive statistics and narrative qualitative analysis. The results showed a subtantial improvement in the average pre-test score from 58 to 96 in the post-test, with an N-Gain of 0.904 904 (high category), proving the effectiveness of educational videos as a learning medium. The video assessment received a very good rating in terms of clarity of content (4.7), clarity in the presentation of the preparation procedure (4.7), video duration (4.9), and usefulness as a business opportunity. Participant satisfaction reached 83.33% (very high category), indicating that the training successfully met their expectations and needs. This activity not only enhances adolescents’ culinary competencies but also empowers the community through the utilization of local potential, and has the potential to be developed sustainably to promote adolescents’ economic self-reliance.